Gender differences in mental health: theoretical approaches, empirical evidence and prospects - Zissi, Anastasia (Psychology: the Journal of the Hellenic Psychological Society, 2022)
This paper aims at, briefly and critically, reviewing the main theoretical approaches in explaining gender differences in mental health by taking three routes. The first route corresponds to a psychological approach that places emphasis on the developmental processes that are taking place at very early childhood, and on issues related to cognitive process and agency formed by gender. The second route corresponds to a social-materialist approach that focusses on the gender structural inequalities and their impact on mental health. The third route corresponds to social-constructionist approaches that places emphasis on discourses through which gender is supervised and enacted. The theoretical premises of each approach are presented together with some of their representative empirical findings. The limitations of each approach are discussed along with the prospects that are opened in psychological theory and research within the gender studies. The psychological studies on gender issues have a low presence in contrast to official reports and contemporary feminist grassroots writings which demonstrate the women’s position deterioration in most of the societies. This deterioration is connected to austerity programs that have transformed women into a “reserve army of unpaid carers” and, to uprising of authoritarian right-wing governments that promote anachronistic legislation and a new type of sexist culture.